Reseña: J. D. Grainger, Antipater’s Dynasty: Alexander the Great’s Regent and his Successors, Barnsley, Pen & Sword Military 2019, 288 pp [ISBN 9781526730886] - Mario Agudo Villanueva (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2019)
Reseña de John D. Grainger, Antipater’s Dynasty: Alexander the Great’s Regent and his Successors, Barnsley, Pen & Sword Military 2019, 288 pp [ISBN 9781526730886].